Influence of Super Absorbent Polymer (SAP) on Mechanical, Durability Properties, and Internal Curing Mechanism of Cement Stabilized Macadam in Desert Environment - Jiachen Ma; Wenhui Zhao; Zewen He; Leilei He; Fengyin Liu; Yana Shi (Advances in Civil Engineering)
Semi-rigid base materials in desert areas are susceptible to fast evaporation of water due to high-temperature and dry environment during construction and curing, leading to insufficient cement hydration and shrinkage cracking, thus affecting the durability of the pavement. In this paper, through indoor simulation of desert curing conditions, based on the study of water absorption and water retention characteristics of super absorbent polymer (SAP), the mix proportion of SAP cement stabilized macadam (CSM) was designed, and the influence of SAP on compaction characteristics was analyzed. The variation of mechanical properties and durability of SAP internal curing CSM was studied. The x-ray diffraction (XRD) and scanning electron microscope (SEM) tests were used to clarify the internal curing effect and microscopic mechanism of SAP on CSM in desert environment. The results show that the mechanical properties of SAP CSM under different curing methods were improved. When the content was 1.0%, the internal curing effect of SAP-B with small particle size was the best in high-temperature curing environment. The dry shrinkage with 1.0% SAP-B was 31.6% lower than that without SAP. SAP can reduce the effect of temperature and humidity on the migration of water inside the specimen. In addition, the incorporation of SAP under high-temperature and drought curing improved the hydration degree of cement, and the microstructure was more compact.